BANALITAS KEJAHATAN KORUPSI DAN AKTIVITAS BERPIKIR - Yosef Keladu Koten (Institut Filsafat dan Teknologi Kreatif Ledalero, 2016)
Corruption, understood as the misuse of entrusted power for private gain, has spread to every corner of Indonesia and become engrained in our daily lives. This is partly caused by the failure to think critically and the fear of judging representatively. It seems that members of our society have become thoughtless and are enslaved by human-made systems or rules. They blindly and uncritically follow the rules to the point where stealing money from those who really need it is considered perfectly normal. Here, corruption is an evil that is called banal. Therefore, following Arendt’s way of thinking, this article suggests the enhancement of critical thinking accompanied by an ability of judging representatively in the midst of the homogenization of the process of thinking as a way of reducing or even eradicating corruption.